DEVELOPMENT, IMPORTANCE, AND PARTICIPATION OF COASTAL TOURISM IN SPAIN - Momirovic, Andjela (The Business of Tourism, 2024)
Coastal tourism is one of the most popular forms of tourism. Spain is a country with a long tradition of this type of tourism and one of the three most popular destinations of this type of tourism in the world. Since the Mediterranean area is the most important for coastal tourism, Spain is visited annually by a large number of tourists, and this economic branch is very important for the economic development of the country. Since the Corona virus pandemic, Spain, as a country that generates significant income from tourism, has again recorded growth and an increased number of tourist visits. The aim of the paper is to show tourist traffic in the coastal part of Spain, its statistical traffic in the period before and after the Corona virus pandemic, then the importance and share of tourism in the overall economic development of the country, but also to consider the perspectives of the development of this type of tourism in the future. To establish what are the biggest problems that are encountered or can be encountered when it comes to this type of tourism and what should be responded to in time and direct development strategies.